Appraisal of anti-smoking advertising by youth at risk for regular smoking: a comparative study in the United States, Australia, and Britain. (23rd July 2003) - Wakefield, M; Durrant, R; Terry-McElrath, Y; Ruel, E; Balch, GI; Anderson, S; Szczypka, G; Emery, S; Flay, B
Abstract : Objective: To compare the similarity in how youth in the United States, Australia, and Britain appraise anti-smoking advertisements with different characteristics. Design: Each participant viewed and evaluated a set of 10 anti-smoking adverts (from an overall total of 50 adverts) in a controlled experimental context using an audience response methodology. A structured telephone interview was completed one week after viewing the adverts, in which recall and engagement with the adverts by participants was evaluated. Subjects: 615 youths who were experimenting with smoking or were susceptible nonsmokers. Main outcome measures: Measures of advert appraisal and engagement. Results: Youth in the United States, Australia, and Britain responded in very similar ways to the same anti-smoking advertisements. In full multivariate models, the target audience of the advert and the advert theme were not related to the main outcome measures employed in this study. However, adverts with visceral negative or personal testimonial executional characteristics were appraised more positively by youths and were more likely to be recalled, thought about, and discussed at follow up one week later. Conclusions: Youths in three different countries responded to anti-smoking advertisements in very similar ways, suggesting that such adverts might be more actively shared among nations. The appraisal of, and engagement with, the anti-smoking adverts, however, varied substantially depending on executional characteristics. In the design of effective anti-smoking adverts, due attention needs to be paid to those characteristics that appear to most engage youth across different social and cultural environments.